Failure Assessment of an In-Service Pressure Vessel with Crack Flow Using Failure Assessment Diagram (FAD) Method - Herucakra, Wira; Simanjuntak, Christina Dewi R.I. (Institut Teknologi Sepuluh Nopember, 2024)
Failure assessment include fatigue assessment was performed for an in-service pressurize equipment utilized to support hydrocarbon proceesing activity as the response of crack-like flaw finding during phase array scanning inspection. The assessment required to ensure the integrity and the safety in the operation of deteriorated pressure vessel. The fitness-for-service assessment in this study are consist of failure assessment using Failure Assessment Diagram (FAD) and the fatigue assessment based on API 579-1/ASME FFS-1. The assessment has demonstrated that the current condition of the equipment was pass the assessment requirement and still has adequate strength and the fatigue damage due to actual operation pressure is an insignificant factor affecting the life of the equipment. This study also investigates the correlation between the geometry of the flaw and the stress increase ratio that is expressed in the exponential function as σC/σR = 4.18e0.82(LD/T^2)